Estudo fitoquímico e avaliação das atividades antimicrobiana, citotóxica e inibitória das catepsinas B e K de Miconia ferruginata (melastomataceae) - (:unkn) unknown (Universidade Estadual de Goiás, 2010)
In this work the phytochemical study and biological tests performed with the organic extract of the leaves of Miconia ferruginata are presented. Among the substances isolated, some were evaluated for potential antimicrobial, cytotoxic and inhibitory uses against cathepsins B and K. One sample was subjected to structural modification in order to verify the structure-activity relationship of the molecules in the sample. Phytochemical study of the ethanol extract of the leaves of M. ferruginata lead to the isolation and identification of 7 substances: the flavones 5,7,4 '-trihydroxy-6,8-dimetilflavone, 5,6,7-trihydroxy-4’-methylflavone and 5-hydroxy-7,4'-dimethoxy-8-methylflavone; the triterpenes ursolic and oleanolic acids; the steroids β-sitosterol and stigmasterol, besides the structural propose for a fourth flavonoid. A mixture of triterpenes ursolic and oleanolic acids inhibited significantly the enzymatic activity of cathepsin B (IC50 = 13.02 μM), displaying also inhibition of four of the five microorganisms where was tested. The mixture of ursolate and oleanolate methyl esters obtained from the reaction with diazomethane of the mixture of triterpenes in the acid form did not show significant results in the antimicrobial assays and enzyme inhibition against cathepsin B. However, showed considerable inhibition against the cathepsin K (IC50 = 1.42 μM) and cell lines of melanoma tumor (MDA-MB-435) and colon cancer (HCT-8). The flavones 5,7,4 '- trihydroxy-6,8-dimetilflavone, 5,6,7-trihydroxy-4'-methoxyflavone and 5-hydroxy-7,4'- dimethoxy-8-methylflavone are reported for the first time in the genus Miconia.
Phytochemical study and evaluation of antimicrobial, citotoxic and inhibitory activities against cathepsins B and K of Miconia ferruginata (melastomataceae)
Keywords: Folhas de miconia ferruginata; Miconia ferruginata; Catepsinas B e K; Química Orgânica; Estudo Fitoquímico; Melastomataceae; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA